3D modelling of intergranular stress corrosion cracking (IGSCC) - Zhang, Y; Marrow, T; Sherry, A (2009)
Intergranular stress corrosion cracking (IGSCC) in austenitic stainless steels occurs as a result of the local grain boundary chromium depletion that can occur through diffusion processes from thermal treatment or fast neutron irradiation. Reliable models of crack nucleation and growth, and their sensitivity to microstructure, are required to underpin lifetime prediction and the development of more resistant materials. A model for 3D IGSCC crack growth has been developed, using finite element analysis, to describe the interactions between the microstructure, the mechanical driving force for cracking, and the kinetics of crack growth. This paper reports the use of this model to investigate the interaction between adjacent cracks, and the sensitivity of short crack behaviour to random variations in microstructure.